Virtual Brand Communities (VMCs): Engagement and Future Intentions - Valenzuela Fernández, Leslier; Martínez Troncoso, Carolina (Estudios de Administración, 2014)
The present paper examines the reasons why by consumers engage into Virtual Brand Communities Generated by Enterprises (VBGE) and Virtual Brand Communities Generated by Consumers (VBGC) and the relationship between type of VBC and the future intentions, commitment and involvement through the development of a theoretical model. A questionnaire with 37 items was developed and applied to 284 participants. The findings indicated significant differences depending on the type of VBC in relation to the motivations of involvement, commitment and future intentions, in order to contribute to the scarce evidence in Latin America.